Artificial dielectric polarizing-beamsplitter and isolator for the terahertz region - Rajind Mendis; Masaya Nagai; Wei Zhang; Daniel M. Mittleman (Scientific Reports, 2017)
Abstract We demonstrate a simple and effective strategy for implementing a polarizing beamsplitter for the terahertz spectral region, based on an artificial dielectric medium that is scalable to a range of desired frequencies. The artificial dielectric medium consists of a uniformly spaced stack of metal plates, which is electromagnetically equivalent to a stacked array of parallel-plate waveguides. The operation of the device relies on both the lowest-order, transverse-electric and transverse-magnetic modes of the parallel-plate waveguide. This is in contrast to previous work that relied solely on the transverse-electric mode. The fabricated polarizing beamsplitter exhibits extinction ratios as high as 42 dB along with insertion losses as low as 0.18 dB. Building on the same idea, we also demonstrate an isolator with non-reciprocal transmission, providing high isolation and low insertion loss at a select design frequency. The performance of our isolator far exceeds that of other experimentally demonstrated terahertz isolators, and indeed, even rivals that of commercially available isolators for optical wavelengths. Because these waveguide-based artificial dielectrics are low loss, inexpensive, and easy to fabricate, this approach offers a promising new route for polarization control of free-space terahertz beams.